Bioacoustic Baselines for Intact Forests - Z. Buřivalová; S. Perea; L. M. Berman; H. S. S. C. Sagar; T. M. Maeda; N. Yoh; G. Ingram; M. Persche; C. Mere‐Roncal; A. Lopera‐Toro; E. Chaboteaux; R. Rumelt; et al. (Global Change Biology, 2026)
Forests are at the frontline of both climate and biodiversity crises: forests are fundamental to the regulation of Earth's atmospheric carbon dioxide levels, and tropical forests alone harbour over half of all terrestrial species. Consequently, forests are at the centre of global efforts to both prevent extinctions of species and sequester carbon to mitigate climate change. Most carbon sequestration initiatives do not measure how effective they are in terms of biodiversity protection, largely because it is expensive, complex and often not required. Compounding this problem is the lack of reliable biodiversity baselines, against which positive changes due to conservation and negative changes due to human pressure could be measured. The Soundscape Baselines Project is a global initiative to collect and analyse bioacoustic baselines in some of the world's remaining intact forests. The baseline data are collected using a modular system of passive acoustic monitoring and ancillary data that can be expanded and integrated with other technologies. It is managed by local teams of scientists, conservation practitioners and community members. Emphasis is on the usability of data and equipment beyond the project, community engagement and building an interconnected network of scientists across forested countries, particularly historically underexplored partnerships between tropical forest countries. In this paper, we describe the initiative and share initial results to demonstrate how the project could be used for biodiversity conservation purposes in the future and outline steps towards operationalization. We also draw a list of priority areas for additional baseline locations across remaining intact forests. We discuss how bioacoustic baselines established now and in the future will become invaluable in a rapidly changing climate and the resulting unprecedented change in Earth's forests. Establishing rigorous biodiversity baselines using bioacoustics and other technologies and approaches through collaborative science is fundamental to ground biodiversity conservation in evidence, equity and transparency.

RFC1-related disorders: A case series of 4-aminopyridine and acetyl-DL-leucine treatment - F. Heindl; A. Traschütz; M. Synofzik; T. Wirth; M. Anheim; A. A. Tarnutzer; A. M. Hartmann; D. Rujescu; I. Giegling; K. Feil; C. Adrion; M. Strupp (The Cerebellum, 2026)
This observational case series summarizes clinical experiences with 4-aminopyridine (4-AP) and acetyl-DL-leucine (ADLL) in patients with RFC1 -related disorders treated under named patient use conditions. Clinical data from 30 patients treated at four university centers in Germany, Switzerland, and France were analyzed. Except for three patients previously enrolled in the ALCAT randomized crossover trial, treatments were initiated as part of routine care and were not standardized for dose or duration. Analyses were based on medical records, including patient-reported outcomes and physician assessments. Four patients from Strasbourg underwent SARA and SDFS assessments before and during treatment; SARA total scores for three ALCAT participants were obtained from the original study dataset. Twelve patients received 4-AP only, seven ADLL only, and eleven both treatments at different time points. Median treatment duration was 29 days for 4-AP and 53 days for ADLL. Subjective improvement was reported in 3/22 patients (13.6%) treated with 4-AP and 3/15 (20.0%) treated with ADLL. Objective gait improvement was observed in 2/13 patients (15.4%) on 4-AP and in 2/10 (20.0%) on ADLL. No effects on downbeat nystagmus were observed. Exploratory analyses revealed no significant differences in SARA total scores between ADLL and placebo or baseline; neither SARA nor SDFS scores improved in Strasbourg patients. Responses to 4-AP and ADLL in RFC1 -related disorders were rare and limited, suggesting that neurodegenerative dysfunction of cerebellar circuits in RFC1 -disease—in contrast to certain genetic cerebellar disorders such as SCA27B—is unlikely to be improved to clinically relevant thresholds by these agents.

Tree Diversity Increases Forest Temperature Buffering via Enhancing Canopy Density and Structural Diversity - Florian Schnabel; Rémy Beugnon; Bo Yang; Ronny Richter; Nico Eisenhauer; Yuanyuan Huang; Xiaojuan Liu; Christian Wirth; Simone Cesarz; Andreas Fichtner; Maria D. Perles‐Garcia; Georg J. A. Hähn; et al. (Ecology Letters, 2025)
Global warming is increasing the frequency and intensity of climate extremes. Forests may buffer climate extremes by creating their own attenuated microclimate below their canopy, which maintains forest functioning and biodiversity. However, the effect of tree diversity on temperature buffering in forests is largely unexplored. Here, we show that tree species richness increases forest temperature buffering across temporal scales over six years in a large‐scale tree diversity experiment covering a species richness gradient of 1 to 24 tree species. We found that species richness strengthened the cooling of hot and the insulation against cold daily and monthly air temperatures and temperature extremes. This buffering effect of tree species richness was mediated by enhanced canopy density and structural diversity in species‐rich stands. Safeguarding and planting diverse forests may thus mitigate negative effects of global warming and climate extremes on below‐canopy ecosystem functions and communities.

No general support for functional diversity enhancing resilience across terrestrial plant communities - Lucrecia Lipoma; Stephan Kambach; Sandra Díaz; Francesco María Sabatini; Gabriella Damasceno; Jens Kattge; Christian Wirth; Scott R. Abella; Carl Beierkuhnlein; Travis R. Belote; Markus Bernhardt‐Römermann; Dylan Craven; et al. (Global Ecology and Biogeography, 2024)
Aim Understanding the mechanisms promoting resilience in plant communities is crucial in times of increasing disturbance and global environmental change. Here, we present the first meta‐analysis evaluating the relationship between functional diversity and resilience of plant communities. Specifically, we tested whether the resilience of plant communities is positively correlated with interspecific trait variation (following the niche complementarity hypothesis) and the dominance of acquisitive and small‐size species (following the mass ratio hypothesis), and for the context‐dependent effects of ecological and methodological differences across studies. Location Global. Time Period 2004–2021. Major Taxa Studied Vascular plants. Methods We compiled a dataset of 69 independent sites from 26 studies that have quantified resilience. For each site, we calculated functional diversity indices based on the floristic composition and functional traits of the plant community (obtained from the TRY database) which we correlated with resilience of biomass and floristic composition. After transforming correlation coefficients to Fisher's Z ‐scores, we conducted a hierarchical meta‐analysis, using a multilevel random‐effects model that accounted for the non‐independence of multiple effect sizes and the effects of ecological and methodological moderators. Results In general, we found no positive functional diversity–resilience relationships of grand mean effect sizes. In contrast to our expectations, we encountered a negative relationship between resilience and trait variety, especially in woody ecosystems, whereas there was a positive relationship between resilience and the dominance of acquisitive species in herbaceous ecosystems. Finally, the functional diversity–resilience relationships were strongly affected by both ecological (biome and disturbance properties) and methodological (temporal scale, study design and resilience metric) characteristics. Main Conclusions We rejected our hypothesis of a general positive functional diversity–resilience relationship. In addition to strong context dependency, we propose that idiosyncratic effects of single resident species present in the communities before the disturbances and biological legacies could play major roles in the resilience of terrestrial plant communities.

Tree demographic strategies largely overlap across succession in Neotropical wet and dry forest communities - Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Dylan Craven; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Bruno Hérault; Catarina C. Jakovac; et al. (Ecology, 2024)
Secondary tropical forests play an increasingly important role in carbon budgets and biodiversity conservation. Understanding successional trajectories is therefore imperative for guiding forest restoration and climate change mitigation efforts. Forest succession is driven by the demographic strategies—combinations of growth, mortality and recruitment rates—of the tree species in the community. However, our understanding of demographic diversity in tropical tree species stems almost exclusively from old‐growth forests. Here, we assembled demographic information from repeated forest inventories along chronosequences in two wet (Costa Rica, Panama) and two dry (Mexico) Neotropical forests to assess whether the ranges of demographic strategies present in a community shift across succession. We calculated demographic rates for >500 tree species while controlling for canopy status to compare demographic diversity (i.e., the ranges of demographic strategies) in early successional (0–30 years), late successional (30–120 years) and old‐growth forests using two‐dimensional hypervolumes of pairs of demographic rates. Ranges of demographic strategies largely overlapped across successional stages, and early successional stages already covered the full spectrum of demographic strategies found in old‐growth forests. An exception was a group of species characterized by exceptionally high mortality rates that was confined to early successional stages in the two wet forests. The range of demographic strategies did not expand with succession. Our results suggest that studies of long‐term forest monitoring plots in old‐growth forests, from which most of our current understanding of demographic strategies of tropical tree species is derived, are surprisingly representative of demographic diversity in general, but do not replace the need for further studies in secondary forests.

Bridging senses of place and mobilities scholarships to inform social-ecological systems governance: A research agenda - Sarah Gottwald; Iga Kołodyńska; Matthias Buchecker; Andrés Di Masso; Nora Fagerholm; Maciej Frąckowiak; Viola Hakkarainen; Katarzyna Kajdanek; Ursula Lau; Lynne C. Manzo; Stefan Ortiz-Przychodzka; Jasmine Pearson; et al. (Applied Geography, 2024)

Quenching of basaltic melts by volatile exsolution - Chris Ballhaus; Josua Pakulla; Richard Wirth; Vladimir Roddatis; Anja Schreiber; Carsten Münker; Frank Wombacher; Andreas Kronz; Raúl O. C. Fonseca; Hanna Cieszynski; Hans-Henning Friedrich (Contributions to Mineralogy and Petrology, 2023)
Normally, volatiles in silicate melts are ephemeral components that escape as gases when the melt reaches fluid saturation. When fluid saturation occurs at elevated pressure, magmatic fluids may have large amounts of oxide solute dissolved, are less volatile, and may resemble viscous gels. In Cyprus we have the rare case that solutes of a magmatic fluid coexist with H 2 O saturated basaltic to boninitic glasses. Quenching of the melts and fluid solutes was induced by fluid segregation. When the fluids exsolved, the liquidus temperature was raised and the melts were left supercooled, while the system temperature remained ± constant. Quenching rates deduced from the morphologies and compositions of quench crystals were high. We analyzed coexisting glasses and fluid solutes for major and trace elements. The fluid mobile trace elements (Rb, K, Pb, Sr) are enriched in both the glasses and fluid solutes. Both endmembers (melt and fluid) have a common parentage and originated within a hydrous mantle source. The glasses have 2.5 ± 0.25 wt.% H 2 O and record residual H 2 O contents left after fluid exsolution was completed. Water contents in glasses correspond to an H 2 O partial pressure (pH 2 O) of 65 ± 10 MPa and an emplacement depth on the seafloor of 6500 ± 1000 m, provided equilibrium was reached between the pH 2 O imposed by the melts and the seawater column. Following fluid exsolution, the degree of supercooling ∆T of the melts relative to the dry MgO-in-melt liquidus temperature was – 65 ± 10 °C. The cooling rate ∆T/t at the time of crystallization of dendritic clinopyroxene crystals can be semi-quantified from the distribution of Al 2 O 3 between metastable clinopyroxene dendrites and melt, to at least – 50 °C h −1 . Toward the end of the article we speculate if other cases exist where quenching was triggered by fluid exsolution. A possible example are spinifex textures deep inside komatiite flows where quenching rates by conductive cooling did not exceed 0.3 to 1 °C h −1 . Our proposition assumes that many spinifex-textured komatiites were hydrous, that they contained H 2 O in quantities sufficient to reach fluid saturation at emplacement pressure, and that spinifex textures formed as a result of supersaturation by fluid loss.

Successional shifts in tree demographic strategies in wet and dry Neotropical forests - Nadja Rüger; Markus E. Schorn; Stephan Kambach; Robin L. Chazdon; Caroline E. Farrior; Jorge A. Meave; Rodrigo Muñoz; Michiel van Breugel; Lucy Amissah; Frans Bongers; Dylan Craven; Bruno Hérault; et al. (Global Ecology and Biogeography, 2023)
Aim Tropical forest succession and associated changes in community composition are driven by species demographic rates, but how demographic strategies shift during succession remains unclear. Our goal was to identify generalities in demographic trade‐offs and successional shifts in demographic strategies across Neotropical forests that cover a large rainfall gradient and to test whether the current conceptual model of tropical forest succession applies to wet and dry forests. Location Mexico and Central America. Time period 1985–2018. Major taxa studied Trees. Methods We used repeated forest inventory data from two wet and two dry forests to quantify demographic rates of 781 tree species. For each forest, we explored the main demographic trade‐offs and assigned tree species to five demographic groups by performing a weighted principal components analysis to account for differences in sample size. We aggregated the basal area and abundance across demographic groups to identify successional shifts in demographic strategies over the entire successional gradient from very young ( Results Across all forests, we found two demographic trade‐offs, namely the growth–survival trade‐off and the stature–recruitment trade‐off, enabling the data‐driven assignment of species to five demographic strategies. Fast species dominated early in succession and were then replaced by long‐lived pioneers in three forests. Intermediate and slow species increased in basal area over succession in all forests, but, in contrast to the current conceptual model, long‐lived pioneers continued to dominate until the old‐growth stage in all forests. The basal area of short‐lived breeders was low across all successional stages. Main conclusions The current conceptual model of Neotropical forest succession should be revised to incorporate the dominance of long‐lived pioneers in late‐successional and old‐growth forests. Moreover, the definition of consistent demographic strategies that show clear dominance shifts across succession substantially improves the mechanistic understanding and predictability of Neotropical forest succession.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Temporal and Spatial Evaluation of Mono(2-ethylhexyl) Phthalate (MEHP) Detection in Common Bottlenose Dolphins (Tursiops truncatus) from Sarasota Bay, Florida, USA - Miranda K. Dziobak; Brian C. Balmer; Randall S. Wells; Emily C. Pisarski; Ed F. Wirth; Leslie B. Hart (Oceans, 2022)
Phthalates are endocrine-disrupting chemicals added to plastics, personal care products, cleaning solutions, and pesticides. Extensive use has led to its exposure to wildlife, including common bottlenose dolphins (Tursiops truncatus) from Sarasota Bay, Florida, USA; however, there are gaps in knowledge regarding whether sample timing or geographic location influence exposure. Dolphins were evaluated for temporal and spatial variability in urinary mono(2-ethylhexyl) phthalate (MEHP) detection (2010–2019). Significant fluctuations in detectable MEHP concentrations were found across the dataset. All samples from 2014 and 2015 (n = 12) had detectable MEHP concentrations; thus, data were classified into cohorts to explore the significance of prevalent MEHP detection (“Cohort 1” (n = 10; 2010–2013), “Cohort 2” (2014–2015), and “Cohort 3” (n = 29; 2016–2019)). Compared to Cohorts 1 and 3, Cohort 2 had higher detectable MEHP concentrations (Dunn’s; p = 0.0065 and p = 0.0012, respectively) and a greater proportion of detectable MEHP concentrations (pairwise comparisons using Benjamini–Hochberg adjustments: p = 0.0016 and p = 0.0059, respectively). MEHP detection also varied across spatial scales. Dolphins with detectable MEHP concentrations had ranges primarily within enclosed embayments, while dolphins with nondetectable MEHP concentrations extended into open waters, potentially indicating geographically linked exposure risk. This study suggests that researchers and management agencies should consider a population’s ranging pattern, geographic habitat characteristics, and sample timing when assessing small cetacean health in relation to contaminant exposure.

Assessment of the efficacy of six field cleaning protocols for hydrocarbon quantification - Emily C. Pisarski; Edward F. Wirth; Paul L. Pennington; Ian Hartwell; Brian S. Shaddrix; David R. Whitall; Dennis A. Apeti; Gregory Baker (Environmental Science and Pollution Research, 2021)

Multi-stressor Effects of Ultraviolet Light, Temperature, and Salinity on Louisiana Sweet Crude Oil Toxicity in Larval Estuarine Organisms - Marie E. DeLorenzo; Peter B. Key; Katy W. Chung; Kaitlin Aaby; Deanna Hausman; Cheldina Jean; Paul L. Pennington; Emily C. Pisarski; Edward F. Wirth (Archives of Environmental Contamination and Toxicology, 2021)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of soil moisture, vegetation and food on adult activity, oviposition and larval development in the tiger beetle, Cicindela albissima Rumpp - C. Barry Knisley; Charles Gowan; Chris Wirth (Journal of Insect Conservation, 2018)

Continental mapping of forest ecosystem functions reveals a high but unrealised potential for forest multifunctionality - Fons van der Plas; Sophia Ratcliffe; Paloma Ruiz‐Benito; Michael Scherer‐Lorenzen; Kris Verheyen; Christian Wirth; Miguel A. Zavala; Evy Ampoorter; Lander Baeten; Luc Barbaro; Cristina C. Bastias; Jürgen Bauhus; et al. (Ecology Letters, 2018)
Humans require multiple services from ecosystems, but it is largely unknown whether trade‐offs between ecosystem functions prevent the realisation of high ecosystem multifunctionality across spatial scales. Here, we combined a comprehensive dataset (28 ecosystem functions measured on 209 forest plots) with a forest inventory dataset (105,316 plots) to extrapolate and map relationships between various ecosystem multifunctionality measures across Europe. These multifunctionality measures reflected different management objectives, related to timber production, climate regulation and biodiversity conservation/recreation. We found that trade‐offs among them were rare across Europe, at both local and continental scales. This suggests a high potential for ‘win‐win’ forest management strategies, where overall multifunctionality is maximised. However, across sites, multifunctionality was on average 45.8‐49.8% below maximum levels and not necessarily highest in protected areas. Therefore, using one of the most comprehensive assessments so far, our study suggests a high but largely unrealised potential for management to promote multifunctional forests.

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

Biodiversity and ecosystem functioning relations in European forests depend on environmental context - Sophia Ratcliffe; Christian Wirth; Tommaso Jucker; Fons van der Plas; Michael Scherer‐Lorenzen; Kris Verheyen; Eric Allan; Raquel Benavides; Helge Bruelheide; Bettina Ohse; Alain Paquette; Evy Ampoorter; et al. (Ecology Letters, 2017)
The importance of biodiversity in supporting ecosystem functioning is generally well accepted. However, most evidence comes from small‐scale studies, and scaling‐up patterns of biodiversity–ecosystem functioning (B‐EF) remains challenging, in part because the importance of environmental factors in shaping B‐EF relations is poorly understood. Using a forest research platform in which 26 ecosystem functions were measured along gradients of tree species richness in six regions across Europe, we investigated the extent and the potential drivers of context dependency of B‐EF relations. Despite considerable variation in species richness effects across the continent, we found a tendency for stronger B‐EF relations in drier climates as well as in areas with longer growing seasons and more functionally diverse tree species. The importance of water availability in driving context dependency suggests that as water limitation increases under climate change, biodiversity may become even more important to support high levels of functioning in European forests.

Petrogenesis of alkaline basalt-hosted sapphire megacrysts. Petrological and geochemical investigations of in situ sapphire occurrences from the Siebengebirge Volcanic Field, Germany - L. C. Baldwin; F. Tomaschek; C. Ballhaus; A. Gerdes; R. O. C. Fonseca; R. Wirth; T. Geisler; T. Nagel (Contributions to Mineralogy and Petrology, 2017)

Allometric equations for integrating remote sensing imagery into forest monitoring programmes - Tommaso Jucker; John Caspersen; Jérôme Chave; Cécile Antin; Nicolas Barbier; Frans Bongers; Michele Dalponte; Karin Y. van Ewijk; David I. Forrester; Matthias Haeni; Steven I. Higgins; Robert J. Holdaway; et al. (Global Change Biology, 2017)
Remote sensing is revolutionizing the way we study forests, and recent technological advances mean we are now able – for the first time – to identify and measure the crown dimensions of individual trees from airborne imagery. Yet to make full use of these data for quantifying forest carbon stocks and dynamics, a new generation of allometric tools which have tree height and crown size at their centre are needed. Here, we compile a global database of 108753 trees for which stem diameter, height and crown diameter have all been measured, including 2395 trees harvested to measure aboveground biomass. Using this database, we develop general allometric models for estimating both the diameter and aboveground biomass of trees from attributes which can be remotely sensed – specifically height and crown diameter. We show that tree height and crown diameter jointly quantify the aboveground biomass of individual trees and find that a single equation predicts stem diameter from these two variables across the world's forests. These new allometric models provide an intuitive way of integrating remote sensing imagery into large‐scale forest monitoring programmes and will be of key importance for parameterizing the next generation of dynamic vegetation models.

Antibiotics as CECs: An Overview of the Hazards Posed by Antibiotics and Antibiotic Resistance - Geoffrey I. Scott; Dwayne E. Porter; R. Sean Norman; C. Hart Scott; Miguel I. Uyaguari-Diaz; Keith A. Maruya; Steve B. Weisberg; Michael H. Fulton; Ed F. Wirth; Janet Moore; Paul L. Pennington; Daniel Schlenk; et al. (Frontiers in Marine Science, 2016)

Dynamics of turbulent western-boundary currents at low latitude in a shallow-water model - C. Q. C. Akuetevi; A. Wirth (Ocean Science, 2015)
The dynamics of low latitude turbulent western-boundary currents (WBCs) crossing the Equator are considered using numerical results from integrations of a reduced-gravity shallow-water model. For viscosity values of 1000 m2 s−1 and greater, the boundary layer dynamics compares well to the analytical Munk-layer solution. When the viscosity is reduced, the boundary layer becomes turbulent and coherent structures in the form of anticyclonic eddies, bursts (violent detachments of the viscous sub-layer, VSL) and dipoles appear. Three distinct boundary layers emerge, the VSL, the advective boundary layer and the extended boundary layer. The first is characterized by a dominant vorticity balance between the viscous transport and the advective transport of vorticity; the second by a balance between the advection of planetary vorticity and the advective transport of relative vorticity. The extended boundary layer is the area to which turbulent motion from the boundary extends. The scaling of the three boundary layer thicknesses with viscosity is evaluated. Characteristic scales of the dynamics and dissipation are determined. A pragmatic approach to determine the eddy viscosity diagnostically for coarse-resolution numerical models is proposed.

Distribution and sources of PCBs (Aroclor 1268) in the Sapelo Island National Estuarine Research Reserve - E. F. Wirth; P. L. Pennington; C. Cooksey; L. Schwacke; L. Balthis; J. Hyland; M. H. Fulton (Environmental Monitoring and Assessment, 2014)

Stand Structure and Recent Climate Change Constrain Stand Basal Area Change in European Forests: A Comparison Across Boreal, Temperate, and Mediterranean Biomes - P. Ruiz-Benito; J. Madrigal-González; S. Ratcliffe; D. A. Coomes; G. Kändler; A. Lehtonen; C. Wirth; M. A. Zavala (Ecosystems, 2014)

Growth of magnesio-aluminate spinel in thin-film geometry: in situ monitoring using synchrotron X-ray diffraction and thermodynamic model - L. C. Götze; R. Abart; R. Milke; S. Schorr; I. Zizak; R. Dohmen; R. Wirth (Physics and Chemistry of Minerals, 2014)

Global relationship of wood and leaf litter decomposability: the role of functional traits within and across plant organs - Katherina A. Pietsch; Kiona Ogle; Johannes H. C. Cornelissen; William K. Cornwell; Gerhard Bönisch; Joseph M. Craine; Benjamin G. Jackson; Jens Kattge; Duane A. Peltzer; Josep Penuelas; Peter B. Reich; David A. Wardle; et al. (Global Ecology and Biogeography, 2014)
Aim Recent meta‐analyses have revealed that plant traits and their phylogenetic history influence decay rates of dead wood and leaf litter, but it remains unknown if decay rates of wood and litter covary over a wide range of tree species and across ecosystems. We evaluated the relationships between species‐specific wood and leaf litter decomposability, as well as between wood and leaf traits that control their respective decomposability. Location Global. Methods We compiled data on rates of wood and leaf litter decomposition for 324 and 635 tree species, respectively, and data on six functional traits for both organs. We used hierarchical Bayesian meta‐analysis to estimate, for the first time, species‐specific values for wood and leaf litter decomposability standardized to reference conditions ( k * wood and k * leaf ) across the globe. With these data, we evaluated the relationships: (1) between wood and leaf traits, (2) between each k * and the selected traits within and across organs, and (3) between wood and leaf k *. Results Across all species k * wood and k * leaf were positively correlated, phylogenetically clustered and correlated with plant functional traits within and across organs. k * of both organs was usually better described as a function of within‐ and cross‐organ traits, than of within‐organ traits alone. When analysed for angiosperms and gymnosperms separately, wood and leaf k * were no longer significantly correlated, but each k * was still significantly correlated to the functional traits. Main conclusions We demonstrate important relationships among wood and leaf litter decomposability as after‐life effects of traits from the living plants. These functional traits influence the decomposability of senesced tissue which could potentially lead to alterations in the rates of biogeochemical cycling, depending on the phylogenetic structure of the species pool. These results provide crucial information for a better representation of decomposition rates in dynamic global vegetation models.

Population pharmacokinetics of peginterferon alfa-2b in pediatric patients with chronic hepatitis C - C. Xu; S. Gupta; G. Krishna; D. Cutler; S. Wirth; C. Galoppo; M. Ciocca; K. Kolz; S. Noviello; V. Sniukiene (European Journal of Clinical Pharmacology, 2013)

A comparison of the strength of biodiversity effects across multiple functions - Eric Allan; Wolfgang W. Weisser; Markus Fischer; Ernst-Detlef Schulze; Alexandra Weigelt; Christiane Roscher; Jussi Baade; Romain L. Barnard; Holger Beßler; Nina Buchmann; Anne Ebeling; Nico Eisenhauer; et al. (Oecologia, 2013)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Evolution of resistance to the Bacillus sphaericus Bin toxin is phenotypically masked by combination with the mosquitocidal proteins of Bacillus thuringiensis subspecies israelensis - Margaret C. Wirth; William E. Walton; Brian A. Federici (Environmental Microbiology, 2010)
Summary Two insecticidal bacteria are used as larvicides to control larvae of nuisance and vector mosquitoes in many countries, Bacillus thuringiensis ssp. israelensis and B. sphaericus . Field studies show both are effective, but serious resistance, as high as 50 000‐fold, has evolved where B. sphaericus is used against Culex mosquitoes. To improve efficacy and deal with even greater potential problems of resistance, we previously developed several recombinant larvicidal bacteria that combine the best mosquitocidal proteins of these bacteria. In the present study, we report laboratory selection studies using our best recombinant strain against larvae of Culex quinquefasciatus . This recombinant, Bti/BsBin, is a strain of B. thuringiensis ssp. israelensis engineered to produce a large amount of the B. sphaericus binary (Bin) toxin, which makes it more than 10‐fold as mosquitocidal as the its parental strains. Here we show that larvae exposed to Bti/BsBin failed to develop significant resistance after 30 successive generations of heavy selection pressure. The highest level of resistance obtained at the LC 95 level was 5.2‐fold, but declined to less than two‐fold at the 35th generation. Testing the selected populations against B. sphaericus alone showed resistance to Bin evolved, but was masked by combination with B. thuringiensis ssp. israelensis . These results suggest that recombinant bacterial strains have improved mosquito and vector management properties compared with the wild‐type strains used in current commercial formulations, and should prove useful in controlling important human diseases such as malaria and filariasis on a long‐term basis, even when used intensively under field conditions.

Effects of chemically spiked sediments on estuarine benthic communities: a controlled mesocosm study - W. L. Balthis; J. L. Hyland; M. H. Fulton; P. L. Pennington; C. Cooksey; P. B. Key; M. E. DeLorenzo; E. F. Wirth (Environmental Monitoring and Assessment, 2010)

Plant traits and wood fates across the globe: rotted, burned, or consumed? - WILLIAM K. CORNWELL; JOHANNES H. C. CORNELISSEN; STEVEN D. ALLISON; JÜRGEN BAUHUS; PAUL EGGLETON; CAROLINE M. PRESTON; FIONA SCARFF; JAMES T. WEEDON; CHRISTIAN WIRTH; AMY E. ZANNE (Global Change Biology, 2009)
Wood represents the defining feature of forest systems, and often the carbon in woody debris has a long residence time. Globally, coarse dead wood contains 36–72 Pg C, and understanding what controls the fate of this C is important for predicting C cycle responses to global change. The fate of a piece of wood may include one or more of the following: microbial decomposition, combustion, consumption by insects, and physical degradation. The probability of each fate is a function of both the abiotic environment and the wood traits of the species. The wood produced by different species varies substantially in chemical, micro‐ and macro‐morphological traits; many of these characteristics of living species have ‘afterlife’ effects on the fate and turnover rate of dead wood. The colonization of dead wood by microbes and their activity depends on a large suite of wood chemical and anatomical traits, as well as whole‐plant traits such as stem‐diameter distributions. Fire consumption is driven by a slightly narrower range of traits with little dependence on wood anatomy. Wood turnover due to insects mainly depends on wood density and secondary chemistry. Physical degradation is a relatively minor loss pathway for most systems, which depends on wood chemistry and environmental conditions. We conclude that information about the traits of woody plants could be extremely useful for modeling and predicting rates of wood turnover across ecosystems. We demonstrate how this trait‐based approach is currently limited by oversimplified treatment of dead wood pools in several leading global C models and by a lack of quantitative empirical data linking woody plant traits with the probability and rate of each turnover pathway. Explicitly including plant traits and woody debris pools in global vegetation climate models would improve predictions of wood turnover and its feedback to climate.

Lectin binding patterns reflect the phenotypic status of in vitro chondrocyte models - S. Toegel; V. E. Plattner; S. Q. Wu; M. B. Goldring; C. Chiari; A. Kolb; F. M. Unger; S. Nehrer; F. Gabor; H. Viernstein; M. Wirth (In Vitro Cellular & Developmental Biology - Animal, 2009)

The Cry48Aa‐Cry49Aa binary toxin from Bacillus sphaericus exhibits highly restricted target specificity - Gareth W. Jones; Margaret C. Wirth; Rose G. Monnerat; Colin Berry (Environmental Microbiology, 2008)
Summary The Cry48Aa/Cry49Aa binary toxin of Bacillus sphaericus was recently discovered by its ability to kill Culex quinquefasciatus mosquito larvae through a novel interaction between its two components. We have investigated the target specificity of this toxin and show it to be non‐toxic to coleopteran, lepidopteran and other dipteran insects, including closely related Aedes and Anopheles mosquitoes. This represents an unusually restricted target range for crystal toxins from either B. sphaericus or Bacillus thuringiensis. Gut extracts from Culex and Aedes larvae show differential processing of the Cry48Aa protein, with the location of cleavage sites in Culex reflecting those previously shown for the activation of Cry4 toxins in mosquitoes. Pre‐activation of Cry48Aa/Cry49Aa with Culex extracts, however, fails to induce toxicity to Aedes larvae. Co‐administration of Cry49Aa with Cry4Aa gives higher than predicted toxicity, perhaps suggesting weak synergism against Culex larvae between Cry49Aa and other three‐domain Cry toxins.

Variations in the mosquito larvicidal activities of toxins from Bacillus thuringiensis ssp. israelensis - Zachariah Ngalo Otieno‐Ayayo; Arieh Zaritsky; Margaret C. Wirth; Robert Manasherob; Vadim Khasdan; Rivka Cahan; Eitan Ben‐Dov (Environmental Microbiology, 2008)
Summary Comparing activities of purified toxins from Bacillus thuringiensis ssp. israelensis against larvae of seven mosquito species (vectors of tropical diseases) that belong to three genera, gleaned from the literature, disclosed highly significant variations in the levels of LC 50 as well as in the hierarchy of susceptibilities. Similar toxicity comparisons were performed between nine transgenic Gram‐negative species, four of which are cyanobacterial, expressing various combinations of cry genes, cyt1Aa and p20 , against larvae of four mosquito species as potential agents for biological control. Reasons for inconsistencies are listed and discussed. Standard conditions for toxin isolation and presentation to larvae are sought. A set of lyophilized powders prepared identically from six Escherichia coli clones expressing combinations of four genes displayed toxicities against larvae of three mosquito species, with levels that differed between them but with identical hierarchy.

Polybrominated Diphenyl Ethers (PBDEs) in Blubber of Free-Ranging Bottlenose Dolphins (Tursiops Truncatus) from Two Southeast Atlantic Estuarine Areas - Patricia A. Fair; Gregory Mitchum; Thomas C. Hulsey; Jeff Adams; Eric Zolman; Wayne McFee; Ed Wirth; Gregory D. Bossart (Archives of Environmental Contamination and Toxicology, 2007)

Cross‐resistance spectra of Culex quinquefasciatus resistant to mosquitocidal toxins of Bacillus thuringiensis towards recombinant Escherichia coli expressing genes from B. thuringiensis ssp. israelensis - Margaret C. Wirth; Arieh Zaritsky; Eitan Ben‐Dov; Robert Manasherob; Vadim Khasdan; Sammy Boussiba; William E. Walton (Environmental Microbiology, 2007)
Summary Sixteen Escherichia coli clones were assayed against susceptible and Bacillus thuringiensis ‐resistant Culex quinquefasciatus larvae. The clones expressed different combinations of four genes from Bacillus thuringiensis ssp. israelensis ; three genes encoded mosquitocidal toxins (Cry11Aa, Cry4Aa and Cyt1Aa) and the fourth encoded an accessory protein (P20). The cross‐resistance spectra of the mosquitoes were similar to the profiles for recombinant B. thuringiensis strains expressing B. thuringiensis toxin genes, but with varied toxicity levels. The toxicity of the recombinants towards resistant mosquito larvae was improved when p20 and cyt1Aa were expressed in combination with cry4Aa and/or cry11Aa . Recombinant pVE4‐ADRC, expressing cry4Aa , cry11Aa , p20 and cyt1Aa , was the most active against the resistant Culex , and resistance levels did not exceed fourfold. These results indicate that B. thuringiensis ssp. israelensis genes expressed in a heterologous host such as E. coli can be effective against susceptible and B. thuringiensis‐ resistant larvae and suppress resistance.

Reconciling Carbon-cycle Concepts, Terminology, and Methods - F. S. Chapin; G. M. Woodwell; J. T. Randerson; E. B. Rastetter; G. M. Lovett; D. D. Baldocchi; D. A. Clark; M. E. Harmon; D. S. Schimel; R. Valentini; C. Wirth; J. D. Aber; et al. (Ecosystems, 2006)

Alpha particle haloes in chlorite and cordierite - L. Nasdala; M. Wildner; R. Wirth; N. Groschopf; D. C. Pal; A. Möller (Mineralogy and Petrology, 2006)

No evidence for DUP25 in patients with panic disorder using a quantitative real-time PCR approach - Johannes Schumacher; Andreas C. J. Otte; Tim Becker; Yuli Sun; Thomas F. Wienker; Brunhilde Wirth; Petra Franke; Rami Abou Jamra; Peter Propping; Jrgen Deckert; Markus M. Nthen; Sven Cichon (Human Genetics, 2003)

Effects of Fipronil and Chlorpyrifos on Endocrine-Related Endpoints in Female Grass Shrimp (Palaemonetes pugio) - D. C. Volz; E. F. Wirth; M. H. Fulton; G. I. Scott; E. Strozier; D. S. Block; J. L. Ferry; S. S. Walse; G. T. Chandler (Bulletin of Environmental Contamination and Toxicology, 2003)

Fire and site type effects on the long-term carbon and nitrogen balance in pristine Siberian Scots pine forests - C. Wirth; E.-D. Schulze; B. Lühker; S. Grigoriev; M. Siry; G. Hardes; W. Ziegler; M. Backor; G. Bauer; N.N. Vygodskaya (Plant and Soil, 2002)

Effects of K ATP channel modulators on acetylcholine release from guinea-pig isolated atria and small intestine - Kilbinger H.; Krause A.; Mang C.; Englert H.; Wirth K. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)

Location of OH groups and oxidation processes in triclinic chloritoid - M. Koch-Müller; V. Kahlenberg; C. Schmidt; R. Wirth (Physics and Chemistry of Minerals, 2000)

Canopy transpiration in a chronosequence of Central Siberian pine forests - Reiner Zimmermann; Ernst‐ Detlef Schulze; Christian Wirth; Ernst‐Eckart Schulze; Kyle C. Mcdonald; Natascha N. Vygodskaya; Waldemar Ziegler (Global Change Biology, 2000)
Summary Tree transpiration was measured in 28, 67, 204 and 383‐y‐old uniform stands and in a multicohort stand (140–430 y) of Pinus sylvestris ssp. sibirica Lebed. in Central Siberia during August 1995. In addition transpiration of three codominant trees was monitored for two years in a 130‐y‐old stand. All stands established after fire. Leaf area index ( LAI ) ranged between 0.6 (28‐y‐old stand) and 1.6 for stands older than 67‐y. Stand xylem area at 1.3 m height increased from 4 cm 2 m −2 (28‐y) to 11.5 cm 2 m −2 (67‐y) and decreased again to 7 cm 2 m −2 in old stands. Above‐ground living biomass increased from 1.5 kg dry weight m −2 (28‐y) to 14 kg dry weight m −2 (383‐y). Day‐to‐day variation of tree transpiration in summer was dependent on net radiation, vapour pressure deficit, and soil water stress. Tree‐to‐tree variation of xylem flux was small and increased with heterogeneity in canopy structure. Maximum rates of xylem flux density followed the course of net radiation from mid April when a constant level of maximum rates was reached until mid September when low temperatures and light strongly reduced flux density. Maximum sap flux density (60 g m −2 s −1 ) and canopy transpiration (1.5 mm d −1 ) were reached in the 67‐y stand. Average canopy transpiration of all age classes was 0.72 ± 0.3 mm d −1. Canopy transpiration ( E ) was not correlated with LAI but related to stand sapwood area SA ( E = − 0.02 + 1.15 SA R 2 ) which was determined by stand density and tree sapwood area.

Grain growth in CaTiO 3 -perovskite + FeO-wstite aggregates - Z. -C. Wang; S. Mei; S. Karato; R. Wirth (Physics and Chemistry of Minerals, 1999)

Above-ground biomass and structure of pristine Siberian Scots pine forests as controlled by competition and fire - C. Wirth; E.-D. Schulze; W. Schulze; D. von Stünzner-Karbe; W. Ziegler; I. M. Miljukova; A. Sogatchev; A. B. Varlagin; M. Panvyorov; S. Grigoriev; W. Kusnetzova; M. Siry; et al. (Oecologia, 1999)

Productivity of forests in the Eurosiberian boreal region and their potential to act as a carbon sink –‐ a synthesis - E. ‐D. Schulze; J. Lloyd; F. M. Kelliher; C. Wirth; C. Rebmann; B. Lühker; M. Mund; A. Knohl; I. M. Milyukova; W. Schulze; W. Ziegler; A. β. Varlagin; et al. (Global Change Biology, 1999)
Summary Based on review and original data, this synthesis investigates carbon pools and fluxes of Siberian and European forests (600 and 300 million ha, respectively). We examine the productivity of ecosystems, expressed as positive rate when the amount of carbon in the ecosystem increases, while (following micrometeorological convention) downward fluxes from the atmosphere to the vegetation (NEE = Net Ecosystem Exchange) are expressed as negative numbers. Productivity parameters are Net Primary Productivity (NPP=whole plant growth), Net Ecosystem Productivity (NEP = CO 2 assimilation minus ecosystem respiration), and Net Biome Productivity (NBP = NEP minus carbon losses through disturbances bypassing respiration, e.g. by fire and logging). Based on chronosequence studies and national forestry statistics we estimate a low average NPP for boreal forests in Siberia: 123 gC m –2 y –1 . This contrasts with a similar calculation for Europe which suggests a much higher average NPP of 460 gC m –2 y –1 for the forests there. Despite a smaller area, European forests have a higher total NPP than Siberia (1.2–1.6 vs. 0.6–0.9 × 10 15 gC region –1 y –1 ). This arises as a consequence of differences in growing season length, climate and nutrition. For a chronosequence of Pinus sylvestris stands studied in central Siberia during summer, NEE was most negative in a 67‐y old stand regenerating after fire (– 192 mmol m –2 d –1 ) which is close to NEE in a cultivated forest of Germany (– 210 mmol m –2 d –1 ). Considerable net ecosystem CO 2 ‐uptake was also measured in Siberia in 200‐ and 215‐y old stands (NEE:174 and – 63 mmol m –2 d –1 ) while NEP of 7‐ and 13‐y old logging areas were close to the ecosystem compensation point. Two Siberian bogs and a bog in European Russia were also significant carbon sinks (– 102 to – 104 mmol m –2 d –1 ). Integrated over a growing season (June to September) we measured a total growing season NEE of – 14 mol m –2 summer –1 (– 168 gC m –2 summer –1 ) in a 200‐y Siberian pine stand and – 5 mol m –2 summer –1 (– 60 gC m –2 summer –1 ) in Siberian and European Russian bogs. By contrast, over the same period, a spruce forest in European Russia was a carbon source to the atmosphere of (NEE: + 7 mol m –2 summer –1 = + 84 gC m –2 summer –1 ). Two years after a windthrow in European Russia, with all trees being uplifted and few successional species, lost 16 mol C m –2 to the atmosphere over a 3‐month in summer, compared to the cumulative NEE over a growing season in a German forest of – 15.5 mol m –2 summer –1 (– 186 gC m –2 summer –1 ; European flux network annual averaged – 205 gC m –2 y –1 ). Differences in CO 2 ‐exchange rates coincided with differences in the Bowen ratio, with logging areas partitioning most incoming radiation into sensible heat whereas bogs partitioned most into evaporation (latent heat). Effects of these different surface energy exchanges on local climate (convective storms and fires) and comparisons with the Canadian BOREAS experiment are discussed. Following a classification of disturbances and their effects on ecosystem carbon balances, fire and logging are discussed as the main processes causing carbon losses that bypass heterotrophic respiration in Siberia. Following two approaches, NBP was estimated to be only about 13–16 mmol m –2 y –1 for Siberia. It may reach 67 mmol m –2 y –1 in North America, and about 140–400 mmol m –2 y –1 in Scandinavia. We conclude that fire speeds up the carbon cycle, but that it results also in long‐term carbon sequestration by charcoal formation. For at least 14 years after logging, regrowth forests remain net sources of CO 2 to the atmosphere. This has important implications regarding the effects of Siberian forest management on atmospheric concentrations. For many years after logging has taken place, regrowth forests remain weaker sinks for atmospheric CO 2 than are nearby old‐growth forests.

HNO3 and PSC Measurements from the Transall: Sequestering of HNO3 in the Winter of 1994/95 - M. Höpfner; C.E. Blom; H. Fishcer; N. Glatthor; T. Gulde; C. Piesch; W. Renger; M. Wirth (Journal of Atmospheric Chemistry, 1998)

MIPAS-Transall Observations of the Variability of CLONO2 during the Arctic Winter of 1994/95 - N. Glatthor; C.E. Blom; T. Blumenstock; H. Fischer; T. Gulde; M. Höpfner; W. Kimmig; C. Piesch; W. Bell; B. Galle; M. Wirth (Journal of Atmospheric Chemistry, 1998)

On the redox control of synthesis of anaerobically induced enzymes in enterobacteriaceae - A. Pecher; F. Zinoni; C. Jatisatienr; R. Wirth; H. Hennecke; A. Bck (Archives of Microbiology, 1983)